Coin Drop Mobile Charger using IR sensor - S.Sandhya; G.Theivanathan; R.Shankari; P.Govindamoorthi (Journal of Electronic Design Engineering, 2017)
The coin based mobile charger developed during the process is providing a featured provision to the public where power is not available for certain inconvenient time in mobiles and it provides a difficult view in the real world. The coin based mobile charger can be easily installed in any mobile phones. In rural area, mobile communication is essential when compared to urban area while urban population use more sophisticated mobiles with advanced technology such as more applications and good power backup for several days. The rural population can buy the pre-owned mobiles that requiring charge frequently. Many times battery becomes dead charge in the middle of any estimate particularlyin convenient and need for ambient times when access to a standard charger is not possible nor available. The coin-based mobile battery chargers are designed to solve this issue. The user has toinsert the mobile phone into one of the universal chargers and insert a coin or two, the phone willthen be given a micro-pulse for charging. It cannot produce full power to the mobile phone which is required. The charging capacity of the mobile is designed with the helpof predefined values to provide the needed charge for emergency purpose. Of course by inserting more coins the charging produced is more. This advantageous lightweight product is designed and fixed to areas forthe growing number mobile users worldwide. A suitable microcontroller(pic) isprogrammed for all the controlling applications. The source for charging isobtained from direct power from battery and in case of non-availability of power.